Electrical conduction of calf-thymus DNA molecules. (10th August 2009) - Abdalla, S.; Jastaniah, S.D.
We present theoretical calculations to explain the behaviour of electrical conduction in calf-thymus DNA molecules trapped between a gap of 10 nm Au electrodes. Our work further explains the experimental I-V data reported for these DNA molecules that shows both large electrical hysteresis and voltage gap. We attribute their data to energy conservation within the molecules and electrons transfer through the metal contact to the molecule.